2017
DOI: 10.1186/s13071-016-1938-y
|View full text |Cite
|
Sign up to set email alerts
|

Lyme disease risk in southern California: abiotic and environmental drivers of Ixodes pacificus (Acari: Ixodidae) density and infection prevalence with Borrelia burgdorferi

Abstract: BackgroundTick-borne diseases, particularly Lyme disease, are emerging across the northern hemisphere. In order to manage emerging diseases and predict where emergence will likely occur, it is necessary to understand the factors influencing the distribution, abundance and infection prevalence of vector species. In North America, Lyme disease is the most common vector-borne disease and is transmitted by blacklegged ticks. This study aimed to explore the abiotic and environmental drivers of density and infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 46 publications
2
51
2
Order By: Relevance
“…A total of 296 adult and 53 nymphal I. pacificus ticks, as well as 72 P. maniculatus and 31 N. fuscipes, were assayed for infection with Borrelia burgdorferi s.l. While infection prevalence was extremely low, as in previous studies conducted in southern California (Lane et al 2013, Padgett et al 2014, Billeter et al 2017,. MacDonald et al 2017, infected hosts were only identified from within the burn extent (two P. maniculatus infected with Borrelia bissettiae; Appendix S1: Table S5) and infected ticks were only identified from within the burn extent in the year following the fire (two nymphs, one infected with Borrelia californiensis and one with B. burgdorferi s.l.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…A total of 296 adult and 53 nymphal I. pacificus ticks, as well as 72 P. maniculatus and 31 N. fuscipes, were assayed for infection with Borrelia burgdorferi s.l. While infection prevalence was extremely low, as in previous studies conducted in southern California (Lane et al 2013, Padgett et al 2014, Billeter et al 2017,. MacDonald et al 2017, infected hosts were only identified from within the burn extent (two P. maniculatus infected with Borrelia bissettiae; Appendix S1: Table S5) and infected ticks were only identified from within the burn extent in the year following the fire (two nymphs, one infected with Borrelia californiensis and one with B. burgdorferi s.l.…”
Section: Resultssupporting
confidence: 59%
“…CA393; Appendix S1: Table S4). No ticks or hosts were infected with the causative agent of Lyme disease, B. burgdorferi s.s. in this study, though infection has been detected in the broader region (MacDonald et al 2017).…”
Section: Resultscontrasting
confidence: 50%
See 3 more Smart Citations